Aedes aegypti Mosquitoes Imported into the Netherlands, 2010 - Julia E. Brown; Ernst-Jan Scholte; Marian Dik; Wietse Den Hartog; Jacob Beeuwkes; Jeffrey R. Powell (Emerging Infectious Diseases, 2011)
During summer 2010, Aedes aegypti mosquitoes were discovered in the Netherlands. Using genetic markers, we tracked the origin of these mosquitoes to a tire shipment from Miami, Florida, USA. Surveillance of tire exports from the United States should be included as part of a comprehensive surveillance system.